OGNIEM I MIECZEM – LEKCJA SZLACHECKIEGO SAVOIR-VIVRE’U - SIKORA, KAZIMIERZ (Slavia Occidentalis, 2020)
Polish linguistic courtesy owes a lot to the gentry’s culture and courtly culture in general. As research suggests, centuries ago the major and specific norms of Polish etiquette (the special position of women) emerged while the noble and courtly origin of the majority of the contemporary forms of address is beyond doubt. Due to the dominant impact of the aristocratic and courtly model of courtesy on the linguistic habits of contemporary Poles and their ancestors, it seemed interesting and useful to present and describe selected elements of Sarmatism’s linguistic etiquette from today’s perspective (with special emphasis placed on words of greetings and farewells) included in Henryk Sienkiewicz’s famous historical novel, Ogniem i mieczem [With Fire and Sword]. This attempt was also stimulated by the book’s cognitive value and the author’s impressive knowledge of the Polish gentry in the mid-17th century, obtained as a result of studies of the literary diaries available to him. Therefore, the attempt made to recreate the world of gentry’s culture and its model of Old Polish etiquette is not just a product of the author’s imagination and it continues to inspire contemporary readers.